Proliferation - Silbaugh, Katharine B. (Columbia Journal of Gender and Law, 2003)
In the spirit of intellectual inquiry, the editors have chosen to hold a symposium asking how the unique mission of the journal is to be justified. Self-assessment is a courageous undertaking. Here we see exemplified one of the great benefits of journals with a well-defined perspective: student editors take the mission of the journal seriously. They are not self-satisfied. They have chosen this perspective, not fallen into it, and they are willing to investigate whether it is worth their commitment. From this comes the simple answer-as long as there are students dedicated to the mission of feminist law journals, authors who seek to publish their work in feminist law journals, and individuals who are interested in reading that work, feminist law journals have a rightful place in the range of institutions that deepen learning. Let me consider two of the objections to women’s law journals, one from feminists, and one more broadly suggested. The first, and most common amongst feminists,’ is a concern about drawing scholarly work away from the mainstream. By separating scholarship from the mainstream we lose the chance to influence and reform it; we do not reach the people who need our perspective the most.